3ΛH and 3Λ[bar]H[bar] production in Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; Oyama, Ken; et al. (Physics letters, 2016)
The production of the hypertriton nuclei HΛ3 and H‾Λ¯3 has been measured for the first time in Pb-Pb collisions at sNN=2.76 TeV with the ALICE experiment at LHC. The pT-integrated HΛ3 yield in one unity of rapidity, dN/dy×B.R.(HΛ3→He3,π−)=(3.86±0.77(stat.)±0.68(syst.))×10−5 in the 0-10% most central collisions, is consistent with the predictions from a statistical thermal model using the same temperature as for the light hadrons. The coalescence parameter B3 shows a dependence on the transverse momentum, similar to the B2 of deuterons and the B3 of 3He nuclei. The ratio of yields S3=HΛ3/(He3×Λ/p) was measured to be S3=0.60±0.13(stat.)±0.21(syst.) in 0-10% centrality events; this value is compared to different theoretical models. The measured S3 is compatible with thermal model predictions. The measured HΛ3 lifetime, τ=181−39+54(stat.)±33(syst.)ps is in agreement within 1σ with the world average value.
Im Titel ist die Zahl "3" hochgestellt, das Zeichen "Λ" ist tiefgestellt
Im Titel haben das zweite "Λ" und das zweite "H" einen Oberstrich
Im Titel ist "lambda" als griechischer Buchstaben dargestellt
Im Titel ist "NN" nach s tiefgestellt, der ganze Ausdruck "s NN" steht unter dem Wurzelsymbol
ALICE collaboration: J. Adam, V. Anguelov, F. Bock, O. Busch, A. Deisting, M.G. Fleck, P. Glässel, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, Y. Wang, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 955 weitere]